Investigation of flow characteristics of coronary slot stents using computational fluid dynamics. (January 2020) - Wang, Xuan Zhi; Masood, Syed H.; Riza, Syed H.; Modi, Harsh
Abstract: Coronary stents are metallic tubes inserted in coronary arteries to treat cardiovascular diseases. Palmaz-Schatz® Stent represents the original design from which many other slot-stent designs have been derived. In this paper, the impact of the geometry of the stent on its flow characteristics was investigated using the computational fluid dynamics (CFD) analysis. Seven design cases were selected for our research investigation, which were divided into three groups: (a) varying the slot length; (b) varying the slot width; and (c) varying the number of slots. Flow characteristics of stents with various geometries were studied by the CFD analysis using ANSYS CFX software. Results of the analysis revealed significant potential relationships between the geometry of the stent and its flow characteristics.